Foundation ActionScript 3.0 for Flash and Flex - Richardson, Darren (Friends of Ed ; Distributed to the Book trade worldwide by Springer-Verlag, 2009)
"This book covers all the essential ActionScript 3.0 techniques from the ground up, allowing you to get up and running quickly and easily"--Resource description page